STUDI PERKEMBANGAN WILAYAH DAN DAYA DUKUNG LINGKUNGAN KEPARIWISATAAN DI WILAYAH YOGYAKARTA UTARA - Muhamad, Muhamad (Sekolah Pascasarjana UGM, 2012)
The growth of tourist regions often indicates a decline of the environmental carrying capacity, includingthe confl ict regarding the use of space and its carrying capacity. The uncontrolled spatial growth andresources use is the result of the increasingly development-oriented policy which cause damage toenvironmental functions. Consideration of the use of space and natural resources advantage is needed inorder to properly consider the issue of carrying capacity. Research is needed to defi ne the proper use oftraffi c signals in connection with the above problem; it is alsoimportant to analyze the regionâs carryingcapacity, which can defi ne its maximum tolerance and fl exibility of capacity. The long-term purpose isto improve touristsâ satisfaction with the area. There are (2) two variables considered: (1) the regionalgrowth; (2) the ecological carrying capacity. The research sample consists of four villages in the Pakemregion (Kaliurang area) and Merapi Volcano National Park (TNGM), DIY.